Astroglial reactivity in the experimental acute hepatic encephalopathy - Shuliatnikova, T. V.; Шулятнікова, Тетяна Володимирівна (My University, 2021)
Liver pathologies associated with severe functional failure in most cases are complicated by potentially reversible but still dangerous neurocognitive disorder termed acute hepatic encephalopathy (AHE) [1]. It is believed that AHE underlying mechanisms are generally focused on the ammonia neurotoxicity. Hyperammonemia mostly target brain astrocytes as they are the only cell population that contain glutamine synthetase and metabolize ammonia along the brain [2].